2019
DOI: 10.1111/jcpp.13137
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of care for children and adolescents with psychosocial problems: a 3‐year prospective cohort study

Abstract: Background: Care for children and adolescents with psychosocial problems is aimed at reducing problems. There may be a relationship between the intensity and duration of care provision and improvement of these outcomes, but evidence on this issue is lacking. We therefore examined the association between care trajectories based on duration and intensity of care for children, and the reduction in psychosocial problems after 3 years. Methods: We obtained a cohort of all children entering psychosocial care in one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
2
1
0
Order By: Relevance
“…Regarding the intensity trajectories, we found that the intensity of care for two out of the three trajectories was particularly high in the first period. These findings corroborate earlier findings showing that the number of services provided was high at the start of care and then decreased (Yampolskaya et al, 2017), and can be interpreted as proving that for a majority of clients, professionals start with rather intensive care. Our finding of a third, persistently low-intensity trajectory is new and calls for further research on its reasons.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regarding the intensity trajectories, we found that the intensity of care for two out of the three trajectories was particularly high in the first period. These findings corroborate earlier findings showing that the number of services provided was high at the start of care and then decreased (Yampolskaya et al, 2017), and can be interpreted as proving that for a majority of clients, professionals start with rather intensive care. Our finding of a third, persistently low-intensity trajectory is new and calls for further research on its reasons.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the reduction in the psychosocial problem levels of children and adolescents with longer care trajectories was relatively smaller. Our finding that care was frequently provided for <3 months confirms that most interventions for children and adolescents with psychosocial problems focus on short-term treatment gains (Mulqueen, Bartley, & Bloch, 2015;Wehry, Beesdo-Baum, Hennelly, Connoly, & Strawn, 2015). Moreover, the SDQ scores of children and adolescents with a short duration of care further improve after care has ended after 3 months.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation